Towards Efficient Water Bottling Operations: A Continuous Improvement Analysis and Deep Learning-Driven Master Production Scheduler - (:unkn) unknown (LACCEI, 2024)
We present a comprehensive solution aimed at enhancing water bottling operations by addressing production planning inefficiencies and order non-compliance, the MPS integrates forecast modelling, inventory control, and production management to streamline ...
Keywords: Producción industrial; Aprendizaje profundo